A COMPREHENSIVE ANALYSIS ON THE EMOTIONAL INTELLIGENCE OF HIGHER SECONDARY SCHOOL TEACHERS - Singh, Irom Premchand; Meitei, Langonjam Chingkheinganba; Devi, K. Rashitombi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Emotional intelligence is the ability to understand and manage one's own and others' emotions; it also includes the ability to perceive and recognize different emotions and handle them appropriately. Strong emotional intelligence enables one to distinguish between different emotions and label them appropriately, recognize their own and others, use emotional information to drive cognition and behavior, and transform their emotions to fit their circumstances. It helps to promote stability, continuity, harmony, and excellent connections in an organizational context, as well as act as a factor in students' academic achievement. The investigators adopted a descriptive survey method for the study. The sample was limited to 100 higher secondary school teachers selected from Senapati and Thoubal districts, Manipur. The Emotional Intelligence Scale tool was used in the study. Nahid Ashraf and Sajid Jamal (2021) designed and developed the tool. The study revealed an average level of emotional intelligence among higher secondary school teachers, with no significant differences observed between male and female, arts and science, or unmarried and married teachers. Whereas there is a significant difference between government and private higher secondary school teachers in the Senapati and Thoubal districts, Manipur.